Keberlanjutan Penyelenggaraan Pilkada Serentak Tahap III Tahun 2018 Yang Ramah Bagi Kaum Penyandang Disbilitas - myamin, ummi (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2017)
Abstract One form and example of democracy run by the state is to hold elections and direct elections. General election is an arena for establishing representative democracy as well as holding periodic government changes.Persons with disabilities are part of this society who also has rights and duties as citizens. One of the rights of incidents of disability is the right to engage in democracy party activities either election or election. Disability is a term that encompasses disruption, limitation of activity, and restriction of participation. This paper aims to describe the implementation of pilkada which has been considered not yet friendly for PwDs. From the data obtained there are still many shortcomings that occurred during the implementation of the pilkada from the early stages of socialization, registration, determination of permanent voters list until the day of voting took place. The results of this paper suggest that some suggestions may be used in the implementation of simultaneous elections that are friendly to disability such as enforcing law enforcement, budget allocation for accessibility and special logistic of persons with disabilities, training for voting officials, . In addition, there should be strict sanctions to areas that do not conduct pilkda in a friendly manner and are not accessible to persons with disabilities  Keywords: Accessibility, Concurrent Pilkada, Disabled Persons